Facing famine: Somali experiences in the famine of 2011. (December 2016) - Maxwell, Daniel; Majid, Nisar; Adan, Guhad; Abdirahman, Khalif; Kim, Jeeyon Janet
Highlights: Somalia experienced the worst famine of the twenty-first century in 2011. People's ability to cope with the famine depended on diversification, mobility and flexibility. People's social connections were instrumental in how well they coped with the famine. Social networks functioned differently in famine—and were not always able to sustain members. Understanding social connectedness will improve famine prevention and response. Abstract: In 2011–12, Somalia experienced the worst famine of the twenty- first century. Since then, research on the famine has focused almost exclusively on the external response, the reasons for the delay in the international response, and the implications for international humanitarian action in the context of the "global war on terror." This paper focuses on the internal, Somali response to the famine. Themes of diversification, mobility and flexibility are all important to understanding how people coped with the famine, but this paper focuses on the factor that seemed to determine whether and how well people survived the famine: social connectedness, the extent of the social networks of affected populations, and the ability of these networks to mobilize resources. These factors ultimately determined how well people coped with the famine. The nature of reciprocity, the resources available within people's networks, and the collective risks and hazards faced within networks, all determined people's individual and household outcomes in the famine and are related to the social structures and social hierarchies within Somali society. But these networks had a distinctly negative side as well—social identity and social networks were also exploited to trap humanitarian assistance, turn displaced people into "aid bait, " and to a large degree, determined who benefited from aid once it started to flow. This paper addresses several questions: How did Somali communities and households cope with the famine of 2011 in the absence of any state-led response—and a significant delay in a major international response? What can be learned from these practices to improve our understanding of famine, and of mitigation, response and building resilience to future crises?